PHYTOCHEMICAL SCREENING, ANTIOXIDANT ACTIVITY AND ANTIMICROBIAL ACTIVITY OF LAGERSTROEMIA PARVIFLORA - A. BOBADE; U. KHANDEKAR; R. GHONGADE (International Journal of Pharma and Bio Sciences, 2013)
The present study was designed to evaluate the Phytochemical composition, antioxidant activity and antimicrobial activity of Lagestroemia parviflora collected from Melghat Forest near Madki Village, Tal- Chikhaldara, Dist- Amravati (M.S) Central region of India. Phytochemical screening was carried out by ‘guide to modern techniques of plant analysis”. Furthermore antioxidant activity of methanolic extract of L. parviflora was investigated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay. Antimicrobial activity of L. parviflora was investigated by Agar disc diffusion assay. The Phytochemical analysis of L. parviflora leaf and seed extracts showed the presence of carbohydrates, alkaloids, flavonoids, cardiac glycosides, phytosterols, steroids, tannins and phenolic compound , and cumarines. The IC50 values for the L.parviflora methanolic leaf extract (IC50= 3482 μg / ml) which was said to be far greater than the standard ascorbic acid (IC50= 2.816 μg / ml). The ethyl acetate extract of L. parviflora leaf showed good inhibition against all six Organisms. The highest inhibition was noted in order of S. aureus (19 mm), E. coli (11 mm), P. aeru (11 mm), P. acne (11 mm). The present study describes the phytochemical profile, antioxidant activity and antimicrobial activity of L. parviflora which will further used for medicinal applications.